Meyvaḻi Rājaṉ Aṉantariṉ kaṭitaṅkaḷ - Rājaṉ Aṉantar, Meyvaḻi, 1901- (Celvaṉ Patippakam, 1981)
Letters by a disciple of Meyvaḻiccālai Āṇṭavar, fl. 1886-1976, founder of Meyvaḻi Hindu syncretic religious movement in Tamil Nadu.